Is bowel preparation necessary for early colonoscopy in patients with suspected colonic diverticular bleeding?: A multicenter retrospective study with propensity score matching analysis - Takahiro Gonai; Yosuke Toya; Norihiko Kudara; Keinosuke Abe; Sera Sawaguchi; Takao Fujiwara; Makoto Eizuka; Minami Hirai; Manami Miura; Jun Urushikubo; Shun Yamada; Tomo Kumei; et al. (DEN Open)
Abstract Objectives There are few reports on bowel preparation for early colonoscopy in patients with suspected colonic diverticular bleeding (CDB). We aim to clarify in a retrospective, multicenter study. Methods In a multicenter retrospective cohort study at 10 institutions, we analyzed clinical features of patients diagnosed with CDB, who underwent early colonoscopy within 24 h. We compared patients who were prepared with polyethylene glycol lavage (PEL) and those without PEL. We evaluated the effects of PEL for early colonoscopy in patients with suspected CDB. Results A total of 129 (53%) underwent under preparation with PEL and 113 patients without PEL. The PEL group was younger, had fewer comorbidities, and had better performance status. After adjusting for these variables with propensity score matching, the PEL group had a significantly shorter hospital stay (7.9 ± 4.7 vs. 10.1 ± 5.2 days; p = 0.001), and a higher cecal intubation rate (91.1% vs. 50.0%; p < 0.001). There were no significant differences in adverse event rates, identification of stigmata of recent hemorrhage, or frequency in endoscopic hemostatic treatment. Conclusions PEL may be preferred for early colonoscopy in patients suspected of having CDB.